Diagnostic techniques in hematological malignancies - Erber, Wendy N., 1957-. (Cambridge University Press, 2010)
"The diagnosis and monitoring of hematological malignancies is complex and requires a systematic approach. Morphology, cell phenotyping, cytogenetics and molecular genetics are essential, and the results must be integrated. Diagnostic Techniques in Hematological Malignancies details the principles and applications of each of these test types in the diagnosis of hematological malignancies in blood and bone marrow. The first section describes the test modalities - including methodological principles, data interpretation and limitations - and is illustrated by clinical examples. The second section focuses on the clinical entities, detailing the most appropriate tests for diagnosis, staging and monitoring of different hematological malignancies and includes test utilization to identify prognostic markers and potential therapeutic targets. With contributions from multiple international experts, this illustrated book is an essential resource for qualified and trainee hematologists, oncologists, and pathologists. It's a practical and useful guide, providing a rational and structured approach to the laboratory assessment of hematological malignancies"--Provided by publisher.